Dental Caries in the Primary Dentition: Assessing Prevalence of Cavitated and Noncavitated Lesions - John J. Warren, DDS, MS; Jed S. Hand, DDS, MHSA; Steven M. Levy, DDS, MPH; H. Lester Kirchner, MS (Blackwell Synergy, 2002)
Dental caries in the primary dentition has received renewed attention in recent years because caries in the primary dentition is predictive of later canes experience, and because of efforts to address early childhood caries. More detailed caries diagnostic criteria have been developed and used for the permanent teeth; however, such criteria have not been widely adopted for caries diagnosis in the primary dentition.